Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1007/s10528-005-6774-2
|View full text |Cite
|
Sign up to set email alerts
|

Low Allozymic Variation in the Bidens pilosa L. Complex (Asteraceae)

Abstract: Bidens alba, B. subalternans, and B. pilosa form a complex group based on their morphological similarities. Bidens pilosa L. and B. subalternans DC. are herbs with a wide distribution in agricultural and disturbed areas. Bidens alba (L.) DC. varies in size from herb to subshrub and has a coastal distribution. Enzyme electrophoresis was used to evaluate genetic diversity in 12 populations of Bidens. All but three loci (Lap-1, Est, and Got) were monomorphic. Est-1 and Got were polymorphic only in B. alba. Lap-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
4
0
1
Order By: Relevance
“…Because only two ALS sequences were observed for region 3, two isoforms could have identical sequence in this region. The ALS isoforms of greater beggarticks showed homology with one ALS isoform from hairy beggarticks agreeing with Grombone-Guaratini et al (2005). According to the authors, greater beggarticks and hairy beggarticks could be considered a single species if the taxonomy group was based only on isozyme data.…”
Section: Resultsmentioning
confidence: 68%
“…Because only two ALS sequences were observed for region 3, two isoforms could have identical sequence in this region. The ALS isoforms of greater beggarticks showed homology with one ALS isoform from hairy beggarticks agreeing with Grombone-Guaratini et al (2005). According to the authors, greater beggarticks and hairy beggarticks could be considered a single species if the taxonomy group was based only on isozyme data.…”
Section: Resultsmentioning
confidence: 68%
“…The evolution of self‐compatibility in plants has long received attention and colonization of new areas is thought to lead to the evolution of selfing or for selection of self‐compatible variants (e.g., Baker, 1955; Stebbins, 1957; Ward et al, 2012; Petanidou et al, 2012). The evidence presented here and by Grombone‐Guaratini et al (2004, 2005) suggests that B. alba may have either latent genetic variation for self‐compatibility not expressed in its native range or the polymorphism exists at such low levels (Barrett and Schluter, 2008) it has not been previously detected (Ballard, 1986). Additionally, we found that the tetraploid species B. alba and the hexaploid species B. pilosa were cross‐compatible, but with low pollen fertility.…”
Section: Discussionmentioning
confidence: 64%
“…Their similarity and overlapping of characters have resulted in imprecise taxonomic characterization, difficulty in establishing clear boundaries, and doubts about the material identification (Grombone-Guaratini et al, 2005a;2005b), even in resistance experiments. These weed species are difficult to control mainly because of their high levels of inbreeding and seed production, and long term survival of seeds on the soil (GromboneGuaratini et al, 2004).…”
Section: Introductionmentioning
confidence: 99%